City playgrounds and their role in the development of physical activity of children and teenagers in interwar Łódź - Sosnowska, Joanna (Contemporary problems of physical and health culture, 2022)
Physical development is an important determinant in child’s general development, mental development included. Physicians, pedagogists, psychologists, teachers, and individuals involved in sport had emphasized the relationship between physical activity and learning as well as its meaning for educational skills even before Poland regained independence. But it was in the interwar period that people became generally aware of the fact that properly directed physical facility supports physical, mental, emotional, and moral development of a human being. Physical activity gained its value as an ingredient of a comprehensively developed personality as a result of, among other things, obligatory education. To raise interest of the younger generation in the maintenance of physical fitness and the development of proper habits or the skill of doing sports became one of the key tasks of school in those years. The purpose of this work is to present an interesting initiative of the Łódź local government which consisted in the opening of a dozen or so playgrounds for children and teenagers in the city. The playgrounds were open to public both in the summer and winter season. They were used by entire families. The city authorities tried to fit them with appropriate sports equipment. Instructors were also employed to organize physical activities for children and teenagers. In the summer of 1931, the Łódź authorities opened 27 playgrounds in several places, including city parks (Poniatowskiego, Źródliska, Kolejowy, and 3 Maja) as well as in Sienkiewicza and Staszica streets and certain other streets in the city.